Influence of membrane active layer properties and support layer properties on organic and inorganic fouling in pressure retarded osmosis (PRO) process - Tan, Joelyn Yi Ying (2015)
Over the recent years, Pressure retarded osmosis (PRO) has drawn many interest due to its potential to harvest renewable and sustainable osmotic energy. However, it was noticed that internal concentration polarization (ICP) and membrane fouling would have a significant impact the performance of the PRO process. Fouling mechanisms and surface cleaning method were done in this study to analyze the influence of membrane surface properties as well as the membrane support layer properties under organic and inorganic fouling. Commercial woven cellulose triacetate (CTA-W), non-woven cellulose triacetate (CTA-NW) and thin-film composite (TFC) membranes were used in the PRO experiment. Active layer towards draw solution (AL-DS) orientation was set-up for this experiment. Humid acid and gypsum were chosen as the model foulant to examine membrane organic fouling and scaling respectively. The results showed that CTA membranes had the smallest flux decline rate during humid acid fouling and scaling in the short run while TFC membrane had the highest flux decline rate. Interestingly, in the long run, all three membranes conveys to the same limiting flux during humid acid fouling. On the other hand, all three membranes conveys to a different limiting flux value during scaling, which was found to be dependent on their individual structural parameters. It was also found that surface cleaning does improves membrane performance to a certain extent. The results illustrated that surface cleaning was more effective after scaling. However, membrane integrity was more severely influenced during scaling for TFC membrane as compared to humid acid fouling. Results in the current study provide significant implications for understanding the mechanisms of PRO fouling, developing strategies for PRO membrane fouling control, and designing a proper membrane for PRO application.